HAK WARIS TERHADAP ANAK ANGKAT (ADOPSI) MENURUT KUH PERDATA (Solusi, 2023)
Adoption is an act of taking someone else's child to be raised and treated as one's own child, based on legal provisions and collective agreements that apply in the community concerned.In this writing, it is used as a discussion regarding the process or procedure for adopting children and the position of adopted children in terms of inheritance. This research uses literature methods and a type of normative juridical research based on legal provisions relating to the problem, it is concluded, The Civil Code does not regulate the issue of adopting children. Regarding the Position and Process of Adopting Children (adoption) is regulated in Articles 5 and 15 of Staatblad No. 129 No. 129. The procedures and requirements for adopting a child are regulated in Chapter III in Articles 12 and 13 of Government Regulation No. 54 of 2007 which states that adopted children are under 18 years of age and the adoptive parents have a family and a maximum age of 55 years. To obtain legal status for an adopted child, a process is carried out through a determination by the local District Court. The position of an adopted child (adopted) is as a legitimate child and can be equated with a child born from a marriage between the husband and wife who adopted him (Staaatsblad No. 129 of 1917, namely articles 11, 12 and 14), to obtain inheritance rights with a will of appointment. inheritance (erfstelling) Article 954 – 956 of the Civil Code and can be determined by a district court judge.